ANALYSIS OF COMPETENCE AND EMOTIONAL INTELLIGENCE ON EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS AN INTERVENING VARIABLE IN THE OFFICE HEAD OF MEDAN BELAWAN DISTRICT - Fauziah Nur Purwaningsih; Mesra B; Elfitra Desy Surya (RADJA PUBLIKA, 2024)
This study aims to analyze the influence of competence and emotional intelligence on employee performance with work motivation as an intervening variable at the Medan Belawan District Office. This study uses a quantitative approach with a survey method by distributing 51 questionnaires to employees as respondents. The research sample was determined using a purposive sampling technique so that the data obtained is relevant to the research objectives. The collected data were analyzed using path analysis techniques to determine the direct and indirect effects between variables. The results of the study indicate that competence has a positive and significant effect on employee work motivation as well as on employee performance. Emotional intelligence has a positive and significant effect on work motivation, but on employee performance through work motivation it has a positive but insignificant effect. Work motivation also has a positive and significant effect on employee performance. In addition, competence and emotional intelligence are proven to have a significant direct effect on employee performance. Thus, work motivation acts as an intervening variable that mediates the effect of competence on employee performance but not with the emotional intelligence variable because the results have a positive but insignificant effect. The findings of this study are expected to be input for leaders in improving employee performance through increasing competence, developing emotional intelligence, and strengthening work motivation.